Bleomycin sclerotherapy following doxycycline lavage in the treatment of ranulas: A retrospective analysis and review of the literature. Issue 5 (October 2021) - Manna, Sayan; Bageac, Devin V; Berenstein, Alejandro; Sinclair, Catherine F; Kirke, Diana; De Leacy, Reade
Objective: A ranula is a mucus-filled salivary pseudocyst that forms in the floor of the mouth, commonly arising from the sublingual or submandibular salivary glands following obstruction or trauma. Complete excision of the injured gland and removal of the cyst content is the first-choice therapy, but has the potential for complications related to injury to nearby structures. As such, minimally invasive approaches such as percutaneous sclerotherapy have been investigated. We aim to contribute to the literature by assessing the efficacy and safety of our technique through our experience with 18 patients over the last decade. Methods: This retrospective study evaluated 18 patients with intraoral and plunging ranulas treated by percutaneous bleomycin ablation. The primary endpoint was the treatment result. Secondary endpoints included bleomycin dosage and complications. Results: The study evaluated 12 males and six females with a median age of 23.5 years (range 13–39 years). At a final follow-up of at least 2 months (6.5±5.5 months), four patients demonstrated complete response (22%) and 14 patients demonstrated residual presence, recurrence, or regrowth of the lesion (78%). There were no statistically significant associations between outcomes and history of prior treatment, number of treatments, and size or type of ranula. No complications were noted. Conclusions: Our findings indicate that bleomycin, while safe for use in various head and neck malformations, is of limited utility in ranula therapy when the offending gland is not addressed primarily.